KEAMANAN JARINGAN PADA PERGURUAN TINGGI - Muhammad Alfian; Rakhmadi Rahman (CV. Denasya Smart Publisher, 2024)
This research analyzes the role of network security in higher education in the face of increasingly complex cyber threats. Using a literature study methodology, this research identified challenges such as malware attacks, phishing, DDoS, and hacking, as well as vulnerabilities such as resource limitations and lack of user awareness. Recommended preventive practices include the implementation of multifactor authentication systems, data encryption, and increased user awareness. The use of firewalls was also highlighted as an important component in protecting the college's digital assets. This research provides guidance for educational institutions to improve their network security infrastructure.